Familial hypercholesterolemia in Brazil: Cascade screening program, clinical and genetic aspects. Issue 1 (January 2015) - Jannes, Cinthia E.; Santos, Raul D.; de Souza Silva, Pãmela R.; Turolla, Luciana; Gagliardi, Ana C.M.; Marsiglia, Julia D.C.; Chacra, Ana P.; Miname, Marcio H.; Rocha, Viviane Z.; Filho, Wilson Salgado; Krieger, Jose E.; Pereira, Alexandre C.
Abstract Background: There is little knowledge about familial hypercholesterolemia in Brazil. This study presents the first results of genetic cascade screening performed in the city of Sao Paulo. Material and methods: Two-hundred and forty-eight suspected index cases were initially included. DNA was extracted from peripheral blood and the complete coding sequence of low-density lipoprotein receptor, exon 7 of proprotein convertase subtilisin/kexin type 9 gene and part of exon 26 of apolipoprotein B genes were sequenced. Multiplex Ligation-dependent Probe Amplification was performed on cases where a causal mutation was not identified through sequencing. After the identification of a causal mutation screening in first-degree relatives was pursued. Results: From 248 index cases, a mutation was found in 125 individuals (50.4%). 394 relatives were included in the cascade screening program and a mutation was identified in 59.4%. Seventy different causal mutations in the low-density lipoprotein receptor gene (97.2%) and 2 in the apolipoprotein B gene (2.8%) were found. No mutations were encountered in the proprotein convertase subtilisin/kexin type 9 gene. Mutations in exons 14 and 4 were the most prevalent and, 10 cases of true homozygotes (8 index cases and 2 relatives) and 1 compound heterozygote were identified. The most frequent mutation found was of Lebanese origin, the p.(Cys681*) mutation in exon 14 (8.5%). Conclusion: Genetic familial hypercholesterolemia cascade screening is feasible in Brazil and leads to identification of a mutation in approximately half of the index cases with higher rates of success in their relatives.